Integrating sport psychology in grassroots football: enhancing performance and well-being - Akbar, Amin; Cahyani, Firunika Intan (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: this research examines the psychological aspects of developing early childhood football players (grassroots football). support from coaches and parents and a holistic training program were critical factors in optimizing a player's potential. Purpose: the research aims to understand how psychological factors influence grassroots football players. this research will likely provide an evaluation of the critical role of sports psychology in developing grassroots football achievements. Methods: this research uses qualitative methods with a grounded theory approach. a total of 10 licensed coaches with a minimum of 5 years-experience in football coaching. this research uses data triangulation, namely open semi-structured interviews, observation, and document analysis, as data collection procedures. the information collected is then analyzed using predetermined themes. Results: the research using the interview method shows that effective motivation methods include positive feedback, setting realistic goals, and creating a competitive but supportive environment. coaches provide praise, set small goals, and create a positive training environment to increase players' self-confidence. in managing player stress, coaches use personal approaches, open communication, and mental training to help athletes overcome pressure. improving social skills in grassroots players is carried out through group exercises that encourage cooperation and participation in community football events. Conclusion: the research results and discussion can be analyzed to show that collaboration between coaches and parents is essential in supporting children's potential, with coaches focusing on developing techniques and understanding of the game and parents providing moral support without excessive pressure. this research confirms the importance of a comprehensive psychological approach to optimally developing early childhood football players.